"Völkisch" Writers and National Socialism - Tourlamain, Guy (2014)
This book provides a view of literary life under the Nazis, highlighting the ambiguities, rivalries and conflicts that determined the cultural climate of that period and beyond. Focusing on a group of writers – in particular, Hans Grimm, Erwin Guido Kolbenheyer, Wilhelm Schäfer, Emil Strauß, Börries Freiherr von Münchhausen and Rudolf Binding – it examines the continuities in völkisch-nationalist thought in Germany from c. 1890 into the post-war period and the ways in which völkisch-nationalists identified themselves in opposition to four successive German regimes: the Kaiserreich, the Weimar Republic, the Third Reich and the Federal Republic. Although their work predated Hitler’s National Socialist movement, their contribution to preparing the cultural climate for the rise of Nazism ensured them continued prominence in the Third Reich. Those who survived into the post-war era continued to represent the völkisch-nationalist worldview in the West German public sphere, opposing both the Soviet and liberal-democratic models for Germany’s future. While not uncontroversial, they were able to achieve significant publishing success, suggesting that a demand existed for their works among the German public, stimulating debate about the nature of the recent past and its effect on Germany’s cultural and political identity and position in the world.